Aktivitas Antibakteri Ekstrak Metanol dari Kulit Batang Kelor (Moringa oleifera Lam.) Terhadap Bakteri Staphylococcus aureus dan Escherichia coli: Antibacterial Activity of Methanol Extracts from The Stem Bark of Moringa oleifera Lam. Against Staphylococcus aureus and Escherichia coli - Nurul Cholifah; Ahmad Ridhay; Pasjan Satrimafitrah; Ruslan; Hardi Ys (KOVALEN: Jurnal Riset Kimia, 2020)
Antibacterial activity of Moringa oleifera Lam. stem bark has been tested against Staphylococcus aureus and Escherichia coli. The extraction of Moringa oleifera Lam. stem bark was used maceration method with methanol solvent and has obtained extract yield of 6.1%. The antibacterial activity test of Moringa oleifera stem bark extracts used a well diffusion method. The concentration of Moringa oleifera stem bark extract was varied to four concentrations of 1% 2% 3% 4% (w/v). The inhibition zone of methanol extract of Moringa oleifera stem bark against Staphylococcus aureus at extract concentrations of 1%, 2%, 3%, and 4% was 10.08 mm, 11.8 mm, 15.00 mm, and 17.02 mm, respectively. The methanol extract of Moringa oleifera stem bark at concentrations of 1%, 2%, 3%, and 4% could also inhibition of Escherichia coli growth with inhibition zone of 14.01 mm, 16.50 mm, 17.09 mm, and 17.10 mm, respectively. Keywords: Moringa Oleifera Lam., Antibacterial, Staphylococcus aureus, Escherichia coli